UV treatment of flexible copper nanowire mesh films for transparent conductor applications - Lonne, Quentin; Endrino, José L.; Huang, Zhaorong (Springer, 2017)
Copper nanowires have the potential to reach and even exceed the indium tin oxide performances as flexible transparent conductive electrodes. However, for a large-scale production, they need to be fabricated in a high-speed, low-cost way, without degrading the flexible substrate. One of the major bottlenecks resides in the post-treatment used to remove organic residues from the surface of the nanowires after forming the transparent electrode, which is necessary to obtain high optoelectronic performances. Here, we propose an ultra-violet irradiation and a subsequent acetic acid bath as an easy, scalable, fast post-treatment. After only 2 min of ultra-violet treatment, followed by 10 min of acid bath, an Rs of 42 Ω sq−1 and a T 550 nm of 87% were measured. Besides, copper nanowire electrodes maintained their high transparency in the range 750–2500 nm, which makes them good candidates for applications such as infrared solar cells.
Keywords: Copper nanowire; Transparent conductive electrodes; Ultra-violet treatment